Implementation of the program process of preparation for starting tank engine under low temperatures - V. I. Yadrov; A. V. Pepelyaev; S. D. Gerasimov; V. S. Weber (Омский научный вестник)
In the presented work, the justification of the need to install a system of the program process of starting the heater on the objects of armored vehicles is given. The analysis of the currently available works on this topic is made. According to the authors, the main shortcomings in the proposed approaches to solving the problem are identified. The article proposes a technical solution that allows to minimize the participation of the driver in the pre-start preparation of the tank engine. A forecast is made for further improvement of the developed system, which allows to significantly raise the level of combat readiness of military units.